PENGARUH RELAKSASI NAFAS DALAM TERHADAP PENURUNAN NYERI DISMENOREA PADA MAHASISWI KEPERAWATAN UM GORONTALO - Harismayanti Harismayanti; Fahmi A. Lihu (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
This research is conducted in University Muhammadiyah Gorontalo and aimed to investigate the influence of relaxation in inside breathing towards decrease of dysmenorrheal painful of nursery students. It is categorized as true experiment design with pre-test and post-test. The population is 215 students are taken are sample with purposive sampling technique. The result shows that there is a significant influence of relaxation in inside breathing towards decrease of dysmenorrheal pinful with p value 0,000 ≤ 0,05. It is tested by using Paired T-Test. Therefore, this research can give solution to women in solving dysmenorrheal painful.